2010
DOI: 10.1186/1472-6963-10-119
|View full text |Cite
|
Sign up to set email alerts
|

Patient and health professional views on rehabilitation practices and outcomes following total hip and knee arthroplasty for osteoarthritis:a focus group study

Abstract: BackgroundThere is worldwide variation in rehabilitation practices after total hip arthroplasty (THA) and total knee arthroplasty (TKA) and no agreement on which interventions will lead to optimal short and long term patient outcomes. As a first step in the development of clinical practice guidelines for post-acute rehabilitation after THA and TKA, we explored experiences and attitudes about rehabilitation practices and outcomes in groups of individuals identified as key stakeholders.MethodsSeparate focus grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
91
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(166 citation statements)
references
References 42 publications
(49 reference statements)
10
91
1
Order By: Relevance
“…The inclusion of individualised exercise specific to each patient aims to increase self-efficacy and empower patients to take an active role as recommended by patient focus groups. 626 Higher levels of self-efficacy at 3 months have been associated with a greater level of functional activity at 9 months after joint replacement, 627 and may enhance adherence to continued home exercise. Involving patients in the design of their rehabilitation may result in better long-term outcome and forms the basis of this function-based group intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of individualised exercise specific to each patient aims to increase self-efficacy and empower patients to take an active role as recommended by patient focus groups. 626 Higher levels of self-efficacy at 3 months have been associated with a greater level of functional activity at 9 months after joint replacement, 627 and may enhance adherence to continued home exercise. Involving patients in the design of their rehabilitation may result in better long-term outcome and forms the basis of this function-based group intervention.…”
Section: Introductionmentioning
confidence: 99%
“…However with the Australian government planning to introduce a personally controlled electronic health record system in mid-2012 [24], participants may have had some exposure to this concept via the media. The importance of inter-professional communication was also noted by Westby during focus groups conducted with rehabilitation patients, which revealed that poor communication between health care settings may negatively impact on patient satisfaction, clinical outcomes, and service coordination [25]. Eldar has also identified the interaction between multidisciplinary professionals as a potential influence on quality of care [6].…”
Section: Discussionmentioning
confidence: 99%
“…This is even more evident in joint arthroplasty clinical practice (Westby 2010) and in physiotherapy practice in general (Jette 2009). Barriers to routine use of outcome measures are multi-faceted and include personal (practitioner) and environmental factors such as access to resources, organizational policies and the practice context (Rivard 2010).…”
Section: Description Of Supporting Evidencementioning
confidence: 99%
“…This is not the case with our novel electrode. Relevance to Physiotherapy Practice: A recent study found that near 40% of patients presenting to a specialized osteoporosis service reported having UI at least once per week (1). This is important because UI can significantly limit a woman's ability to be physically active and is an independent risk factor for falls and low trauma fractures in older women.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation